A relation between number of integral points, volumes of faces and degree of the discriminant of smooth lattice polytopes - Dickenstein, Alicia Marcela (2012)
We present a formula for the degree of the discriminant of a smooth projective toric variety associated to a lattice polytope P, in terms of the number of integral points in the interior of dilates of faces of dimension greater or equal than [dim P / 2].